The roots of the quadratic equation are 13 and 3. The quadratic equation can be written as (x - 13)(x - 3) = 0

(x - 13)(x - 3) = 0

=> x^2 - 13x - 3x + 39 = 0

=> x^2 - 16x + 39 = 0

**The required quadratic equation is x^2 - 16x + 39 = 0**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now